Strain-gradient mediated local conduction in strained bismuth ferrite films - Ming-Min Yang (Nature Portfolio, 2019)
In semiconductors strain gradients can separate light induced electron-hole pairs via the flexo-photovoltaic effect. Here the authors show that this effect can also account for the enhancement of the photoconduction in certain phase regions at the morphotropic phase boundary in Bismuth Ferrite films.